Caffeine secretion into breast milk. - Tyrala, E E (1979)
Serum and milk concentrations of caffeine were measured in 5 breast-feeding mothers after a standardised oral dose of caffeine. Peak concentrations of caffeine in serum and milk were attained 60 minutes later. Binding of caffeine by constituents of serum and breast milk was low (25 and 3.2% respectively). In breast milk, caffeine binding is associated with the cream layer, and correlates with the butter fat content. Caffeine does not diffuse freely into breast milk and concentrations in milk are lower than in maternal serum.